Resting and Exercise-Induced Left Atrial Hypertension in Patients With Atrial Fibrillation: The Causes and Implications for Catheter Ablation - Sramko, Marek; Wichterle, Dan; Melenovsky, Vojtech; Clemens, Marcell; Fukunaga, Masato; Peichl, Petr; Aldhoon, Bashar; Cihak, Robert; Kautzner, Josef (JACC. Clinical electrophysiology, 2017)
OBJECTIVES: The aim of this paper was to investigate the prevalence of resting and exercise-induced left atrial hypertension (LAH) in patients with nonvalvular atrial fibrillation (AF), association of the LAH with other cardiac abnormalities, and its implications for AF catheter ablation. BACKGROUND: The clinical role of LAH in patients with established AF is largely unknown. METHODS: Patients scheduled for catheter ablation of AF (n = 240; age 60 ± 10 years; 67% men, 62% paroxysmal AF) underwent detailed echocardiography, assessment of quality of life (QoL), left atrial (LA) voltage mapping, and measurement of the LA pressure at rest and during isometric handgrip exercise. After ablation they were followed for AF recurrence for 16 ± 6 months. RESULTS: Resting and exercise-induced LAH (mean LA pressure >15 mm Hg) occurred in 15% and 34% of the patients, respectively. Both the patients with resting and exercise-induced LAH had typical features of latent heart failure with preserved ejection fraction associated with advanced LA structural and functional remodeling. AF recurred after ablation in 45% of the patients. LAH was an independent risk factor for arrhythmia recurrence (hazard ratio: 1.7, 95% confidence interval: 1.2 to 2.2). The patients with LAH had worse baseline QoL, but they benefited significantly more from a successful ablation than the patients without LAH. CONCLUSIONS: Presence of either resting or exercise-induced LAH identified AF patients with a distinct clinical profile, extensive LA substrate, and different clinical response to catheter ablation. Stratification of AF patients based on the LA exercise hemodynamics could help in the future to tailor the ablation strategy.
Keywords: recidiva; Humans; Atrial Function, Left; remodelace síní; síňový tlak; lidé středního věku; heart failure with preserved ejection fraction; Hypertension; Quality of Life; atrial remodeling; Hand Strength; Female; rizikové faktory; Aged; senioři; lidé; Atrial Fibrillation; Atrial Remodeling; Heart Atria; kvalita života; katetrizační ablace; srdce - funkce levé síně; síla ruky; Follow-Up Studies; ženské pohlaví; Male; Middle Aged; atrial substrate; hypertenze; atrial pressure; exercise hemodynamics; srdeční síně; Atrial Pressure; Recurrence; Exercise; substrate ablation; mužské pohlaví; Catheter Ablation; cvičení; následné studie; fibrilace síní; Risk Factors